Fortified excreta pellets for agriculture - Nikiema, Josiane; Cofie, Olufunke O.; Impraim, Robert; Drechsel, Pay (2012)
This paper describes the pelletization process of fecal sludge-based fertilizers. The equipment used for the process was fabricated locally in Ghana. Each fertilizer product was individually used for the production of cylindrical pellets. From the current study, the binding material type (cassava starch, either pregelatinized or pretreated by gamma irradiation, or kaolin clay) and concentration (0 to 10 % in mass) as well as moisture content (20-47%) appeared to be the most critical factors during pellets production. It was noticed that the higher the binder concentration, the higher the stability of pellets. This study confirmed that cassava starch is a preferred binding material and that fixing its concentration at 1-3 % could be enough during the pelletization process. The pellets produced in this project had 7.5 to 7.7 mm in diameter, but their length distribution varied depending on the material used.